TEACHER STRATEGIES IN OVERCOMING BULLYING BEHAVIOR USING BEHAVIOR METHODS - Wirda Indah; Johannes Johny Koynja; Hesti Mustika Ati (International Journal of Teaching and Learning, 2024)
Bullying behavior is aggressive and oppressive behavior, whether in the form of direct physical action or attacking through words. Bullying behavior does not only occur in education, but can also occur in almost all areas of life such as politics, economics, social and culture. Bullying in schools is a global problem and a social issue that negatively affects the lives and future career paths of school children. The occurrence of bullying behavior is inseparable from various factors. This study describes the factors that influence the occurrence of bullying behavior, including family factors, environmental factors, and peer groups. The teacher's strategy in overcoming bullying behavior is to use behavioristic methods. The steps taken in the behavior counseling process include the first assessment where the counselor encourages the client to express the problem he is experiencing. Assessment is carried out to identify which techniques to choose and in accordance with the behavior that you want to change. Second, goal setting is a step to formulate counseling goals. Third, implementation techniques, namely determining and implementing counseling techniques used to achieve the desired behavior which is the goal of counseling. Fourth, termination evaluation, namely conducting assessment activities whether the counseling activities carried out have led to and achieved results in accordance with the counseling objectives.